Culturality in mathematics education – a comparative study - Owens, Kay (NOMAD Nordic Studies in Mathematics Education, 2008)
The purpose of this paper is to draw upon extensive multicultural experiences and research to present some key aspects of effective multicultural teaching and learning. With an emphasis on cultural context and language, the discussion uses examples from Sweden and Australia, although experience and research in other cultures have informed the perspectives. Aspects of culture that are relevant to mathematics and approaches that maintain culture are emphasised. An emphasis on national values and language is also influencing schooling but strategies that take account of diversity of language and culture are provided.